Business processes reconstruction within the supply chain in the context of outsourcing - Якимишин, Лілія Ярославівна (Technology audit and production reserves, 2015)
The article deals with the terms of making solution by a production enterprise concerning the commitment of key operation areas to outsourcing. It has been determined that this solution is sound when, within the delivery chain, the enterprise – outsourcer is its participant. Enterprise integration based on partnership and joint strategy complied with the strategies of chain supply participants will contribute to the establishment of synergy effect, increase the competitiveness and new level of satisfying the consumer demands. It has also bun determined that the business processes reconstruction within the delivery chain should be implemented in the context of guasi-soureing of its key competences, which demands product supply analysis, and shortage consequence assessment, introducing actions regarding coordination of business strategy with functional strategies and delivery chain strategy, developing the algorithm of solution making for the application of outsourcing in the area of product manufacture, namely manufacturing of the necessary components of the final product.